Analisis Pelaksanaan ANC terpadu pada Masa Pandemi Covid-19 di Puskesmas Kalasan - Melly Nirma Syahriani; Mufdilah Mufdilah; Sulistyaningsih Sulistyaningsih (Politeknik Kesehatan Kemenkes Mamuju, 2022)
The Covid-19 pandemic has resulted in changes to integrated antenatal care services. Existing problems can be seen from the input including human resources, facilities and infrastructure, funding sources, policies and SOPs. Processes and outputs include coverage of pregnant women's visits, handling of complications in pregnancy. The purpose of this study was to analyze in depth the implementation of integrated ANC during the Covid-19 pandemic at the Kalasan Health Center. This study uses a qualitative method with a holistic case study approach (holistic single-case study). The number of informants in the study was 10 informants. The technique of taking informants is purposive sampling. Data collection is done by looking at the SOP for the Implementation of the Integrated ANC, visit reports, in-depth interviews online. The instrument in this study used semi-structured online interview guidelines. Data analysis used thematic analysis. The results of the analysis of the problems of implementing an integrated ANC during the Covid-19 pandemic found 3 themes, namely input problems, process problems, and output problems. The conclusions of this study are the limitations of human resources, infrastructure, sources of funds, changes in SOP policies, the fear of patients to check their pregnancies, restrictions on patients and service time, changes in services, limitations in handling pregnancy complications, decreased coverage of pregnant women visits.